The effect of general anesthesia on the test–retest reliability of resting-state fMRI metrics and optimization of scan length - Vedaei, Faezeh; Alizadeh, Mahdi; Romo, Victor; Mohamed, Feroze B.; Wu, Chengyuan (Frontiers in Neuroscience, 2022)
Resting-state functional magnetic resonance imaging (rs-fMRI) has been known as a powerful tool in neuroscience. However, exploring the test-retest reliability of the metrics derived from rs-fMRI BOLD signal is essential particularly in the studies of patients with neurological disorders. Here, two factors including the effect of anesthesia and scan length have been estimated on reliability of rs-fMRI measurements. A total of 9 patients with drug-resistant epilepsy (DRE) of requiring interstitial thermal therapy (LITT) were scanned in two states. The first scan was performed in an awake state before surgery in the same patient. The second scan was performed two weeks later under general anesthesia necessary for LITT surgery. At each state, two rs-fMRI sessions were obtained that each one lasted 15 minutes, and the effect of scan length was evaluated. Voxel-wise rs-fMRI metrics including amplitude of low frequency fluctuation (ALFF), fractional amplitude of low frequency fluctuation (fALFF), functional connectivity (FC), and regional homogeneity (ReHo) were measured. Intraclass correlation coefficient (ICC) was calculated to estimate the reliability of the measurements in two states of awake and under anesthesia. Overall, it appeared that reliability of rs-fMRI metrics improved under anesthesia. From the 15-min data, we found mean ICC values in awake state including 0.81, 0.51, 0.65, and 0.84 for ALFF, fALFF, FC, and ReHo respectively as well as 0.80, 0.59, 0.83, and 0.88 for ALFF, fALFF, FC, and ReHo respectively under anesthesia. Additionally, our finding revealed that reliability increases as the function of scan length. We showed that the optimized scan length to achieve less variability of rs-fMRI measurements was 3.1 – 7.5 minutes shorter in an anesthetized, compared to wakeful state.